The Challenge Program on Water and Food: Volta Basin Development Challenge inception workshop - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2011)
The current phase (2010-2013) of the Challenge Program on Water and Food (CPWF) research is addressing the Volta Basin Development Challenge (VBDC) which has been defined as “integrated management of rainwater and small reservoirs for multiple purposes”. The research-for-development program is designed to explore the institutional, socio-economic and technical aspects of small reservoir development and maintenance within a wider rainwater management system in the Volta Basin to maximize water for food and ecosystem services. The purpose of the inception workshop was to review and assess all VBDC projects for coherence and integration towards achieving the overall goal. Secondly it provided an opportunity to launch the research agenda, share our plans and approaches with a wider, relevant stakeholder group, and to obtain important feedback which can be fed into the research process. The key question to address during the workshop was: “what are the lessons learned in the inception phase of VBDC research and how would these lessons shape project implementation in the next phase?”. It was expected that the workshop would contribute to ensuring relevance of the research agenda, as well as strengthening the integration of the five VBDC projects and their teams.